2017
DOI: 10.1016/j.oraloncology.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone in head and neck cancer patients with microvascular reconstruction: No benefit, more complications

Abstract: The use of dexamethasone in oral cancer patients with microvascular reconstruction did not provide a benefit. More major complications, especially infections, occurred in patients receiving dexamethasone. Our data thus do not support the use of peri- and postoperative dexamethasone in oropharyngeal cancer patients undergoing microvascular reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In their previous study of the same study population, the authors found that the use of dexamethasone was associated with more complications, especially regarding postoperative infections. 18 Postoperative pain management relieves suffering, can accelerate earlier mobilization, and decrease hospital stay duration and costs. Many published reports in different surgical fields have described the analgesic effect of steroids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their previous study of the same study population, the authors found that the use of dexamethasone was associated with more complications, especially regarding postoperative infections. 18 Postoperative pain management relieves suffering, can accelerate earlier mobilization, and decrease hospital stay duration and costs. Many published reports in different surgical fields have described the analgesic effect of steroids.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of preoperative medical data, surgical data, TNM classifications, parameters during surgery, and complications rated can be found in the authors' previous study. 18 Surgery was performed under standard balanced anesthesia. Patients were given antibiotics targeted for days, starting with cefuroxime 1.5 g  3 IV and metronidazole 500 mg 1  3 IV on induction of general anesthesia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their data thus did not support the use of peri-and post-operative dexamethasone in oropharyngeal cancer patients undergoing microvascular reconstruction. 38 Dexamethasone 8-10 mg is associated with a significantly greater peri-operative increase in blood glucose compared with a 4 mg dose. This model estimated the increase in post-operative glucose to be 25 mg/dL higher over 24 hours with dexamethasone 8-10 mg than with 4 mg (95% confidence limits, 18-32 mg/dL).…”
Section: Adverse Effects Of Dexamethasonementioning
confidence: 96%
“…10 We have previously shown that the use of perioperative DEX increases the incidence of major complications in patients with HNC undergoing microvascular reconstruction, which could also have affected patient survival. 11 Thus, the purpose of the present study was to investigate whether the use of perioperative DEX would influence the short-term survival of patients with HNC. The second aim was to assess the causes of death and the factors associated with mortality during long-term follow-up of patients who had undergone surgery and reconstruction for HNC.…”
mentioning
confidence: 99%